Influence of Age and Sex on Meat Fatty Acid Profiles and Cholesterrol in Various Strains of Japanese Quail Meat - M., Shashi Kumar; K., Sudhakara Reddy; K. , Kondal Reddy; Chaturvedi , Anurag; N , Krishnaih. (Journal of Meat Science, 2011)
Major fatty acid and Cholesterol content of meat of different strains of Japanese quails were estimated. Palmitolic acid content (per cent) in meat of Japanese quail of black spotted strain (6.62) was significantly higher than those belonging to brown and white strains but the linoleic acid content was higher in brown strain (20.83), when compared to black spotted (19.68) and white (20.04) strains. The palmitolic acid, stearic acid and oleic acid contents (per cent) showed an increase with age while the palmitic acid and linoleic acid content decreased. The linoleic acid content was significantly higher in female birds than males. The total meat unsaturated fatty acid content was significantly higher in brown strain (69.51) than white (68.98) and black spotted (68.78) strains. The meat cholesterol content (mg/100g) in Japanese quail belonging to white strain (75.71) was lower compared to brown (76.75) and black spotted strains (76.31) and was lower in males (74.76) compared to females (76.63).